2023
DOI: 10.3390/rs15184465
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Area Index Inversion of Spartina alterniflora Using UAV Hyperspectral Data Based on Multiple Optimized Machine Learning Algorithms

Hua Fang,
Weidong Man,
Mingyue Liu
et al.

Abstract: The leaf area index (LAI) is an essential biophysical parameter for describing the vegetation canopy structure and predicting its growth and productivity. Using unmanned aerial vehicle (UAV) hyperspectral imagery to accurately estimate the LAI is of great significance for Spartina alterniflora (S. alterniflora) growth status monitoring. In this study, UAV hyperspectral imagery and the LAI of S. alterniflora during the flourishing growth period were acquired. The hyperspectral data were preprocessed with Savitz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The FDS transformation can limit the noisy backgrounds, such as soil, to a certain extent [75], and the optimal band combinations of OS may pay attention to the sensitivities of some specific bands to the anthocyanin value. In comparison, the optimal band combinations of FDS may attach more importance to the trends of the spectral curves [27]. Additionally, the band combinations selected for the same vegetation index were not identical for different wheat growth stages, mainly associated with different sensitivities that anthocyanin values generated to spectra at various stages of winter wheat.…”
Section: Bsm: Screening For Optimal Sensitive Bands and Band Combinat...mentioning
confidence: 97%
See 1 more Smart Citation
“…The FDS transformation can limit the noisy backgrounds, such as soil, to a certain extent [75], and the optimal band combinations of OS may pay attention to the sensitivities of some specific bands to the anthocyanin value. In comparison, the optimal band combinations of FDS may attach more importance to the trends of the spectral curves [27]. Additionally, the band combinations selected for the same vegetation index were not identical for different wheat growth stages, mainly associated with different sensitivities that anthocyanin values generated to spectra at various stages of winter wheat.…”
Section: Bsm: Screening For Optimal Sensitive Bands and Band Combinat...mentioning
confidence: 97%
“…Moreover, it has been shown that using VIo has achieved favorable outcomes in hyperspectral inversion. Fang et al [27] respectively screened five VIo3 (ESI, MCARI, SIPI, TSI, NSI) based on OS, FDS, and second-order differential data, using hyperspectral data of Spartina alterniflora, which captured the vegetation information that could not be covered by the traditional VIs and improved the sensitivity of the VIs to LAI. Deng et al [28] searched for the optimal combination of bands for VIs in a study that used hyperspectral to assess wheat stripe rust.…”
Section: Introductionmentioning
confidence: 99%
“…PLSR is particularly advantageous when internal variables exhibit high linear relationships and is suitable for scenarios where the number of variables exceeds the number of samples, as well as handling multicollinearity issues [16]. SVR is based on statistical learning theory, using kernel functions to transform the initial input space into a new feature space with higher dimensions, thus converting nonlinear regression problems into linear relationships, and performs exceptionally well with smaller samples [49]. RF is an ensemble learning method that combines multiple decision trees through bootstrap sampling.…”
Section: Model Construction and Evaluation Metricsmentioning
confidence: 99%